Claiming geothermal water: Critical legal geography and the scalar politics of hot spring development in China. Issue 2 (18th January 2019) - Feng, Dan; Li, Peng
Abstract : This article contributes to the ongoing scrutiny of conflicts over nature with respect to the legal realm. We argue that legal geographies have been central to the boom in geothermal water extraction in China and its environmental and social effects. We examine the contesting of the legal definition of geothermal water and how it is embedded in the creation and production of China's hot spring landscape. Specifically, we focus on the biophysics of this particular natural resource to examine the scalar politics of how local governments grab natural resources, and the ways in which they produce socio‐economic consequences. The analysis illustrates the significance of critical legal geography in current political ecology studies, and suggests paying close attention to the contradictory and slippery legal practices involved in the governance and commodifying of nature. Abstract : This article examines the contesting of the legal definition of geothermal water and how it is embedded in the creation and production of China's hot spring landscape. Specifically, we focus on the biophysics of this specific natural resource to examine the scalar politics of how local governments grab natural resources and the ways in which they produce socio‐economic consequences.